2000
DOI: 10.1042/cs0980501
|View full text |Cite
|
Sign up to set email alerts
|

Increased left atrial thrombin generation in mitral stenosis is not reflected in arterial prothrombin fragment 1+2 levels

Abstract: A proportion of patients with mitral stenosis have increased left atrial thrombin generation, with elevated left atrial but normal peripheral venous levels of prothrombin fragment 1+2 (F1+2). Whether this pattern of left atrial and venous F1+2 levels is related to limited spillover of F1+2 from the left atrium into the systemic circulation, or to washout of increased left atrial F1+2 production into the arterial circulation with subsequent systemic clearance, is unclear. We examined the relationship between ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
2

Year Published

2000
2000
2001
2001

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 7 publications
1
13
2
Order By: Relevance
“…Contrary to the assertion of Li-Saw-Hee and Lip that thrombogenesis in cardiac disease is likely to be a generalized process, we believe that there is now abundant evidence from our group [1][2][3][4] and others [5][6][7] which supports the existence of a localized increase in left atrial coagulation activity in mitral stenosis. Moreover, this coagulation activation is not primarily due to atrial fibrillation as it is also observed in patients with sinus rhythm who have left atrial spontaneous echo contrast [1,7].…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to the assertion of Li-Saw-Hee and Lip that thrombogenesis in cardiac disease is likely to be a generalized process, we believe that there is now abundant evidence from our group [1][2][3][4] and others [5][6][7] which supports the existence of a localized increase in left atrial coagulation activity in mitral stenosis. Moreover, this coagulation activation is not primarily due to atrial fibrillation as it is also observed in patients with sinus rhythm who have left atrial spontaneous echo contrast [1,7].…”
contrasting
confidence: 99%
“…mia has been associated with a hypercoagulable state, with abnormalities of haemostasis, platelets and endothelial dysfunction, which are independent of aetiology and underlying structural heart disease, and are altered by antithrombotic therapy and cardioversion [3]. We were pleased to note that Peverill et al [1] only found a reduction in left atrial F1j2 levels in the patients with increased regional left atrial thrombin generation who were in sinus rhythm, and not among the patients who were in atrial fibrillation, which is in keeping with the highly prothrombotic or hypercoagulable state in this arrhythmia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the conclusion that mitral valve dilatation produced a sustained decrease in left atrial coagulation activity is confounded by two major factors. Secondly, the assumption of Yamamoto et al [7] that arterial F1j2 levels are representative of left atrial levels may not be correct, and has not been confirmed in a subsequent study [27]. Secondly, the assumption of Yamamoto et al [7] that arterial F1j2 levels are representative of left atrial levels may not be correct, and has not been confirmed in a subsequent study [27].…”
Section: Discussionmentioning
confidence: 94%
“…Peverill and colleagues [1] recently reported differences in levels of prothrombin fragment 1j2 (F1j2) in blood obtained from the left atrium, the femoral artery and the femoral vein from 36 patients with mitral stenosis. They aimed (i) to compare arterial and venous levels of F1j2 in patients with normal clotting times, (ii) to examine and compare the relationship between arterial and venous levels of F1j2 in patients with and without increased left atrial thrombin generation, and (iii) to compare the relationship between arterial and venous levels of F1j2 in patients with a prolonged or a normal international normalized ratio (INR).…”
mentioning
confidence: 99%